Analisis Kriminologi: Persepsi dan Motivasi Penulis Fanfiction Erotis BL Thailand di X - Amalia Putri Astuti; Monica Margaret (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study examines the primary motivations of authors in creating erotic slash fanfiction using Thai boys-in-love actors on the app X. Adopting a qualitative approach with in-depth interviews and thematic analysis, and interpreted through the lens of Symbolic Interactionism Theory and Labeling Theory, this study highlights how authors understand and interact with this phenomenon. The findings indicate that authors perceive their work as a form of self-expression, art, and entertainment, despite being aware of the potential for labeling as pornography or violating legal norms. Their primary motivation stems from the fulfillment of personal imagination and self-satisfaction, which is significantly strengthened by the validation and support of a supportive online community. This community also plays a crucial role in shaping unwritten norms and providing psychological buffers against potential external negative views. Authors demonstrate various strategic responses, including the use of disclaimers and a realistic acceptance of societal perceptions. The implications of this study emphasize the importance of a nuanced understanding of online subcultural practices, fostering digital literacy, and suggesting a wise and adaptive approach to content regulation in the digital age. This study also provides insights into how authors of erotic fanfiction on online platforms like X interact with popular cultural values and gender identity. The authors in this study are not only connected to their communities but also engaged in a broader process of identity construction through the characters they create. The Thai boy-love actor, a frequent inspiration in their work, serves as a symbol that reinforces the representation of non-heteronormative relationships, providing space for a more free and inclusive exploration of sexual identity.